Reflections on a Health System's Telemedicine Marathon - Lawrence R. Wechsler; Srinath Adusumalli; Mary Elisabeth Deleener; Ann Marie Huffenberger; Gregory Kruse; C. William Hanson III (Telemedicine Reports, 2020)
The coronavirus disease 2019 (COVID-19) public health emergency necessitated changes in health care delivery that will have lasting implications. The University of Pennsylvania Health System is a large multihospital system with an academic medical center at its core. To continue to care for patients with and without COVID-19, the system had to rapidly deploy telemedicine. We describe the challenges faced with the existing telemedicine infrastructures, the central mechanisms created to facilitate the necessary conversions, and the workflow changes instituted to support both inpatient and outpatient activities for thousands of providers, many of whom had little or no experience with telemedicine. We also discuss innovations that occurred as a result of this transition and the future of telemedicine at our institution.